Overview of F18-FDG uptake patterns in retroperitoneal pathologies: imaging findings, pitfalls, and artifacts. - Pathak, Priya; Abandeh, Laith; Aboughalia, Hassan; Pooyan, Atefe; Mansoori, Bahar (Abdominal Radiology, 2024)
Introduction: Retroperitoneum can be the origin of a wide variety of pathologic conditions and potential space for disease spread to other compartments of the abdomen and pelvis. Computed tomography (CT) and magnetic resonance imaging (MRI) are often the initial imaging modalities to evaluate the retroperitoneal pathologies, however given the intrinsic limitations, F18-FDG PET/CT provides additional valuable metabolic information which can change the patient management and clinical outcomes. We highlight the features of retroperitoneal pathologies on F18-FDG PET/CT and the commonly encountered imaging artifacts and pitfalls. The aim of this review is to characterize primary and secondary retroperitoneal pathologies based on their metabolic features, and correlate PET findings with anatomic imaging. Conclusion: Retroperitoneal pathologies can be complex, ranging from oncologic to a spectrum of non-oncologic disorders. While crosse-sectional imaging (CT and MRI) are often the initial imaging modalities to localize and characterize pathologies, metabolic information provided by F18-FDG PET/CT can change the management and clinical outcome in many cases. (a) Brown fat activation on F18-FDG PET. Axial fused PET image of the abdomen shows hypermetabolic foci in the bilateral perinephric fat (arrows). (b) Adrenal metastasis in a 78-year-old woman with serous ovarian carcinoma. Axial fused PET/CT of the abdomen shows intense uptake in the new left adrenal lesion (arrow), with FDG uptake intensity markedly higher than the liver. (c)Axial contrast-enhanced CT abdomen shows the lobulated mildly enhancing left adrenal metastasis (circle).